IMPLEMENTATION OF CONSISTENT PILKADA IN MALANG DISTRICT FROM PRECAUTIONARY PRINCIPLES - Fitria Esfandiari; Arsyi Manggali Arya Putra (Audito Comparative Law Journal (ACLJ), 2021)
The implementation of the Regional Head Election (Pilkada) which was held simultaneously on December 9, 2020 in Malang Regency is a step towards realizing democracy directly in the region. In contrast to the implementation of pilkada in previous years, this year's regional elections were held in the midst of the Covid 19 pandemic. With the issuance of PKPU Number 5 of 2020, it was decided to continue. This research raises the problem of how the simultaneous regional elections in Malang Regency are viewed from the principle of prudence and how to project the strengthening of democracy through simultaneous regional elections in Malang Regency. The method used is the descriptive normative method by reviewing literature that is in line with existing problems with statutory regulations as well as statutory approaches and literature. The conclusion from this research is that the stages of the Pilkada implementation which are carried out with the principle of prudence are an effort to limit the spread of the Covid 19 virus. On the other hand, it is also an effort to continue to fulfill the constitutional rights of the people in the regions in the Pilkada. Furthermore, if it is related to the simultaneous regional election scheme in 2027, Malang Regency in its development is able to play a very significant role for democracy in the regions with. The technology and information approach must be seen as an effort to solve democracy in the regions in the pandemic era.